2017
DOI: 10.1158/1940-6207.capr-16-0223
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of γ- and δ-Tocopherols on Estrogen-Stimulated Breast Cancer In Vitro and In Vivo

Abstract: Estrogens have been implicated as complete carcinogens for breast and other tissues through mechanisms involving increased cell proliferation, oxidative stress and DNA damage. Because of their potent antioxidant activity and other effects, tocopherols have been shown to exert anti-tumor activities in various cancers. However, limited information is available on the effect of different forms of tocopherols in estrogen-mediated breast cancer. To address this, we examined the effects of α-, γ- and δ-tocopherols a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…Dietary administration of δ‐T and γ‐T, but not α‐T, was shown to inhibit tumorigenesis in ER‐positive breast cancer, while did not provide protective effects against ER‐negative and HER‐2 positive breast cancer, suggesting that the chemopreventive effects are due to estrogen‐mediated and ER‐dependent mechanisms 97 . δ‐T and γ‐T have been shown to inhibit estrogen‐stimulated breast cancer tumor growth 101 . In a breast cancer model, mice with MCF‐7 xenograft tumors implanted with estrogen, treatment with γ‐T, δ‐T, or γ‐TmT (2 g/kg diet) significantly reduced tumor volume and tumor weight, and inhibited cell proliferation‐related genes such as cyclin D1 and c‐Myc as well as estrogen‐related genes TFF/pS2, cathepsin D, and progesterone receptor 101 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dietary administration of δ‐T and γ‐T, but not α‐T, was shown to inhibit tumorigenesis in ER‐positive breast cancer, while did not provide protective effects against ER‐negative and HER‐2 positive breast cancer, suggesting that the chemopreventive effects are due to estrogen‐mediated and ER‐dependent mechanisms 97 . δ‐T and γ‐T have been shown to inhibit estrogen‐stimulated breast cancer tumor growth 101 . In a breast cancer model, mice with MCF‐7 xenograft tumors implanted with estrogen, treatment with γ‐T, δ‐T, or γ‐TmT (2 g/kg diet) significantly reduced tumor volume and tumor weight, and inhibited cell proliferation‐related genes such as cyclin D1 and c‐Myc as well as estrogen‐related genes TFF/pS2, cathepsin D, and progesterone receptor 101 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 99%
“…δ‐T and γ‐T have been shown to inhibit estrogen‐stimulated breast cancer tumor growth 101 . In a breast cancer model, mice with MCF‐7 xenograft tumors implanted with estrogen, treatment with γ‐T, δ‐T, or γ‐TmT (2 g/kg diet) significantly reduced tumor volume and tumor weight, and inhibited cell proliferation‐related genes such as cyclin D1 and c‐Myc as well as estrogen‐related genes TFF/pS2, cathepsin D, and progesterone receptor 101 . Furthermore, decreased the levels of estrogen‐induced oxidative stress and nitrosative stress markers, 8‐oxo‐dG, and nitrotyrosine, as well as the DNA damage marker, phosphorylated histone 2A variant X (γ‐H2AX), were evident 101 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that δ-T, γ-T and γ-TmT suppress N -methyl- N -nitrosourea induced mammary tumor growth in Sprague Dawley rats (9,10). Recently, the tumor inhibitory effects of δ-T, γ-T and γ-TmT in MCF-7 xenografts supplemented with estrogen have been demonstrated (26). August-Copenhagen Irish (ACI) rats exhibit 80-100% tumor incidence upon prolonged exposure to estrogen (27), providing a physiologically relevant model for long-term cancer prevention studies.…”
Section: Introductionmentioning
confidence: 99%